KATEGORI ADOPTER PETANI DALAM PROSES DIFUSI INOVASI LTBS PADA USAHATANI PADI SAWAH DI DESA ATOLANU KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Jumriati Jumriati; Salahuddin Salahuddin; Mardin Mardin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
Rodent infestation remains a major challenge in lowland rice farming due to its high level of crop damage, resulting in significant yield losses and reduced agricultural productivity. The Linear Trap Barrier System has been introduced as an environmentally friendly and effective rodent management innovation; however, its adoption among farmers remains inconsistent. This study aimed to analyze farmers' adopter categories in the diffusion process of LTBS innovation in lowland rice farming in Atolanu Village, Lambandia District, East Kolaka Regency, Indonesia, with particular emphasis on the dynamics of innovation dissemination based on Rogers' Diffusion of Innovations theory. A descriptive qualitative approach was employed in this study. Informants were selected using the snowball sampling technique, involving rice farmers, agricultural extension agents, and key actors engaged in the innovation diffusion process. Data were collected through field observations, in-depth interviews, documentation, and literature review. Data were analyzed using the interactive model consisting of data reduction, data display, and conclusion drawing, complemented by social network analysis using UCINET VI software to map communication patterns among farmers. The findings revealed that the LTBS diffusion process occurred gradually through five adopter categories, consisting of one innovator (4.76%), three early adopters (14.29%), four early majority adopters (19.04%), ten late majority adopters (47.62%), and three laggards (14.29%). The innovator acted as the pioneer by acquiring information from outside the village and electronic media before disseminating the innovation to early adopters through interpersonal communication. The early adopters served as key intermediaries who strengthened the innovation's legitimacy and facilitated its dissemination to the early majority. Subsequently, the late majority adopted the innovation after observing convincing empirical evidence and receiving social encouragement from their community, whereas the laggards tended to retain conventional practices due to limited resources, risk perceptions, and strong adherence to traditional farming practices. The success of LTBS innovation diffusion was influenced not only by the technological advantages of the innovation but also by the effectiveness of interpersonal communication, the strength of social networks, the presence of opinion leaders, and support from local institutions. Therefore, strategies to enhance innovation adoption should focus on strengthening the capacity of agricultural extension agents, optimizing the role of pioneer farmers, and empowering farmer groups as collective learning platforms to accelerate the sustainable diffusion of agricultural innovations.